2022
DOI: 10.1093/bjsopen/zrac118
|View full text |Cite
|
Sign up to set email alerts
|

The value of intraoperative parathyroid hormone monitoring in patients with primary hyperparathyroidism and varying baseline parathyroid hormone levels

Abstract: Background When applying intraoperative parathyroid hormone monitoring (IOPTH) to patients with primary hyperparathyroidism (PHPT), there are established criteria predicting biochemical cure in patients with basal parathyroid hormone (PTH) levels in the medium range (100–400 pg/ml); however, there is a challenge concerning patients with low (less than 100 pg/ml) or high (more than 400 pg/ml) basal PTH levels. The aim of this study was to investigate the value of the ‘Vienna criterion’ applied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…A recent meta‐analysis has reported that 18 F‐fluorocholine is more sensitive than 11 C‐methionine for detecting the affected gland in PHPT 44 . Finally, intraoperative PTH monitoring (IOPTH) is a sensitive and specific predictor of surgical cure, and can be a useful tool in cases where preoperative imaging results are equivocal 45–47 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent meta‐analysis has reported that 18 F‐fluorocholine is more sensitive than 11 C‐methionine for detecting the affected gland in PHPT 44 . Finally, intraoperative PTH monitoring (IOPTH) is a sensitive and specific predictor of surgical cure, and can be a useful tool in cases where preoperative imaging results are equivocal 45–47 …”
Section: Discussionmentioning
confidence: 99%
“…44 Finally, intraoperative PTH monitoring (IOPTH) is a sensitive and specific predictor of surgical cure, and can be a useful tool in cases where preoperative imaging results are equivocal. [45][46][47] A limitation of our study is that patients did not all receive all imaging modalities as part of their diagnostic work-up for PHPT. A formal head-to-head comparison between all imaging modalities within our cohort was, therefore, not possible.…”
Section: Sensitivitymentioning
confidence: 99%
“…Second, several studies have shown that the preoperative localization rates of imaging modalities are lower in these patients, as the lesions tend to be smaller in size and weight [ 2 ]. Third, IOPTH assays may have a lower specificity and a higher false-negative rate in these patients, as the baseline PTH levels are already low [ 28 ]. It should be noted that the success rate of surgical resection depends not only on the accuracy of the preoperative imaging modality but also on the surgeon’s skill.…”
Section: Discussionmentioning
confidence: 99%